Applied Structural Equation Modeling in SMARTPLS: A Beginner’s Roadmap to SEM, Measurement Models, and Path Testing (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study develops a beginner-oriented roadmap for applying PLS-SEM in SmartPLS, addressing the gaps between theory and practical application.Methods: Using an instructional design-based approach, simulated datasets with six latent constructs were analysed in SmartPLS 4 to demonstrate key steps in measurement validation, structural path testing and model evaluation.Results: The demonstrations shows both acceptable and problematic validity outcomes, highlighting how reliability, discriminant validity and model fit can be refined. The results are pedagogical, not statistically generalizable and shows methodological learning rather than empirical findings. Conclusion: This study provides novice researchers’ and educators with a structured, practice-oriented guide that transforms common PLS-SEM pitfalls into learning opportunities, enhancing methodological literacy.